Javanese Cultural Values of the Yogyakarta Palace in the Film ‘Marak: Mresani Panji Sekar’ - Yulian Dinihari; Zuriyati Zuriyati; Ninuk Lustyantie (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Film is one of the effective and popular media in cultural learning, both local and foreign cultures. The film that is used as the object of research by the researcher is the film 'Marak: Mresani Panji Sekar'”. This film becomes an interesting study material because it explains the Javanese culture of the courtiers of the Yogyakarta Palace who will focus more on culture in the film. This research uses descriptive qualitative research method. Analyzing cultural values by means of observation and study of documents in films in an effort to gain an overview and understanding of what is being studied. The values obtained are in the form of many values contained in it, namely the values of honor, trust, politeness, responsibility, and art. Describe the Javanese values of the Yogyakarta Palace which are shown in the film 'Marak: Mresani Panji Sekar' and reveal and understand the meaning contained in these traditional values.Keywords: Film, Values, Javanese Cultural